FAKTOR - FAKTOR YANG MEMPENGARUHI NIAT UNTUK BERTRANSAKSI SECARA ONLINE PADA TOKO ONLINE - Dwi Islamiyati; Nugraeni Nugraeni (Jurnal Akuntansi, 2014)
This study aims to determine the effect of privacy, security, trust, and experience the internet on the intention to transact online. The study subjects were 200 students from various colleges in the city of Yogyakarta. The research method was a questionnaire survey instrument. Analysis of the data used is test convergent validity, discriminant and composite reliability test. Results showed that :There is the influence of trust and perceptions of risks to attitude. There is influence between security, trust and privacy to the perception of risk. There is the influence of attitudes and perceptions of risk on the intention to transact online. There is a relationship between the experience of using the internet and subjective norm on the intention to transact online. There is a positive effect between behavioral control on the intention to transact online. Keywords : Privacy, Security, Trust, Internet experience, Intention, and online transactions